Effect of domain manipulation in the Staphylococcal Phage endolysin, Endo88, on lytic efficiency and host range - Krishnan, Melvina; Tham, Hong Yun; Wan Nur Ismah, Wan Ahmad Kamil; Yusoff, Khatijah; Song, Adelene Ai-Lian (Springer, 2024)
The bacteriophage endolysin Endo88 targeting Staphylococcus aureus PS88 consists of the CHAP and Amidase-2 enzymatic domains and one SH3b targeting domain. In this study, the effects of domain manipulations on Endo88 functionality were determined. Three truncated mutants of Endo88 (CHAP, CHAPAmidase and CHAPSH3) and two chimeras (CHAPAmidase-Cpl7Cpl7 and Endo88-Cpl7Cpl7) containing the Cpl7Cpl7 targeting domains of the streptococcal LambdaSa2-ECC endolysin were cloned in E. coli (pET28a), expressed, and then purified. Lytic efficiency and host range were assessed through plate lysis assays and turbidity reduction assays. Endo88 required all domains for maximum functionality, with activity detected against Staphylococcus aureus PS88 (host strain), S. aureus Mu50 (VISA), CoNS (Staphylococcus epidermidis and Staphylococcus hominis), and Enterococcus faecalis. The truncated constructs maintained the original host range but with reduced lytic efficiency. The Amidase-2 and SH3b domains are interdependent in maximizing functionality. The chimera constructs demonstrated reduced functionality, without activity against Streptococcus agalactiae in both assays. This study provides insights into domain function in a staphylococcal endolysin, which could enable the development of prospective engineered antimicrobials against multidrug-resistant pathogens.